Pengembangan Sistem Informasi Akademik Sekolah Menengah Kejuruan (SMK) (Studi pada SMK Muhammadiyah 1 Kemlagi) - Muhammad Taftiyan Ilham Akbar; Satrio Agung Wicaksono; Faizatul Amalia (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2021)
SMK Muhammadiyah 1 Kemlagi is a private school in Mojokerto Regency which was established in 2016. When the research was conducted, SMK Muhammadiyah 1 Kemlagi was still using Microsoft Excel and Microsoft Word program for data processing. That's software did not connected to the database system, so there were often problems in managing data in a large amount. Many such as out of sync data and long and difficult data searches caused by many separate documents. This study aims to solve this problem by developing an information system to process school academic data. The information system developed is called the academic information system of SMK Muhammadiyah 1 Kemlagi or abbreviated as SIAKAD SMK MUTU. The information system developed is web-based and built using the PHP programming language with the Codeigniter framework with MVC architecture and MySQL database program. The system development method applies the waterfall model and the system modeling uses the UML (Unified Modeling Language) language, system testing uses blackbox testing and user acceptance test (UAT). The results of the blackbox test stated that the 20 function test cases found the validity of 100% and the system was running according to the stated specifications, the results of the user acceptance test (UAT) were found to be 82.9% of the 10 (ten) participants tested. Referring to the test results, it can be concluded that SIAKAD SMK MUTU is declared valid and very acceptable to users.